Role of biostimulants in mitigating the effects of climate change on crop performance - Bhupenchandra, Ingudam; Chongtham, Sunil Kumar; Devi, Elangbam Lamalakshmi; R., Ramesh; Choudhary, Anil Kumar; Salam, Menaka Devi; Sahoo, Manas Ranjan; Bhutia, Tshering Lhamu; Devi, Soibam Helena; Thounaojam, Amarjit Singh; Behera, Chandana; M. N., Harish.; et al. (Frontiers in Plant Science, 2022)
Climate change is a critical yield–limiting factor that has threatened the entire global crop production system in the present scenario. The use of biostimulants in agriculture has shown tremendous potential in combating climate change–induced stresses such as drought, salinity, temperature stress, etc. Biostimulants are organic compounds, microbes, or amalgamation of both that could regulate plant growth behavior through molecular alteration and physiological, biochemical, and anatomical modulations. Their nature is diverse due to the varying composition of bioactive compounds, and they function through various modes of action. To generate a successful biostimulatory action on crops under different parameters, a multi–omics approach would be beneficial to identify or predict its outcome comprehensively. The ‘omics’ approach has greatly helped us to understand the mode of action of biostimulants on plants at cellular levels. Biostimulants acting as a messenger in signal transduction resembling phytohormones and other chemical compounds and their cross–talk in various abiotic stresses help us design future crop management under changing climate, thus, sustaining food security with finite natural resources. This review article elucidates the strategic potential and prospects of biostimulants in mitigating the adverse impacts of harsh environmental conditions on plants.